Para Rasul dan Gereja Rasuli - Chandra Gunawan (Veritas : Jurnal Teologi dan Pelayanan, 2017)
How should a contemporary reader understand the complexities of the early church? Many scholars utilize a religious studies perspective to understand the early church concluding that the church grew as a direct result (synthesis) of group conflicts (in particular, the Pauline and Petrine communities). This essay approaches the early church from a different paradigm. Using theological analysis, the author concludes that although the early church contained elements of diversity, she exhibits significant unity. The Catholic Epistles (the letters of James, Peter, John, and Jude) are independent letters that are interconnected by the Jerusalem tradition, and the theologies of these letters reflect the unique character of the early church. Therefore, it is important that NT scholars should give more attention to the Catholic Epistles so that the early church can be understood from a more constructive perspective.